(untitled) (e-Boletim da Física, 2019)
It has a degree, a master’s degree and a doctorate from the University of the State of Rio de Janeiro (UERJ). He has postdated at the Brazilian Center for Physical Research (CBPF). Has experience in the field of condensed matter physics, phase transition to finite temperature such as condensation of Bose-Eistein. He developed a study on BCS-BEC crossover (CBPF). His research is now centered on the study of gauge theories for gravitation, effective gauge theories with violation of Lorentz symmetry, and effects of spin-orbit interaction on a more fundamental physics via the weakly relativistic boundary of the Dirac equation.